Perancangan dan Strategi Tata Kelola TI Menggunakan COBIT 2019 pada PT. XYZ - Iqbal Habib Al Baqi; Winarni; Taswanda Taryo (Universitas Pamulang, 2026)
XYZ faces unstructured and reactive IT governance challenges, characterized by data silos and slow operational application response times. This gap hinders strategic alignment and operational efficiency within an institution that has significant responsibility for public services. This study uses the COBIT 2019 framework to design a systematic and contextual governance strategy. The novelty of this research lies in the holistic integration of the 10 Design Factors in the public sector with a high security risk profile that has not been widely explored. A descriptive qualitative methodology was applied through in-depth interviews, observations, and document studies with key informants from the managerial to operational levels. The analysis follows the COBIT 2019 Design Guide workflow and is validated through triangulation techniques and member checking. The analysis results show a focus on service stability with high security risks (40%) and strict compliance (30%). Of the 40 objectives, 14 priority Governance and Management Objectives (GMO) were identified, focusing on risk optimization and external compliance. The research produced a three-phase strategic roadmap aligned with the organization's objectives and the Personal Data Protection Law regulations. This strategy transforms IT governance at PT. XYZ into a more structured, accountable, and adaptive framework.